"Tribute to Mother Practitioner", an original and genuine historical celebration of Healthcare Assistants Alicante (1959-1970) - José Antonio Ávila Olivares (Universidad de Alicante, 2015)
After highlighting the initiatives and original contributions of the Practitioners' Council of Alicante to the history of festivities and institutional commemorations of the profession at provincial and national levels, this paper provides an anthropological view of the most original festivity, that has the most social influence: the "Mother Practitioner's Tribute", which has been held for over more than a decade (1959-1970) in the province of Alicante to honor the eldest mother of the group of referees. It explains in detail the festivity's philosophy and the way of celebrate it are detailed. The circumstances, people and places concerned in each one of the tributes' editions, which information has been obtained investigating both professional press and general newspapers.